PROACTIVE MARKETING AS A COMPONENT OF THE STRATEGY FOR INCREASING THE COMPETITIVENESS OF CORPORATE BUSINESS ENTITIES - Okhrimenko, Alla; Melnyk, Iryna; Sеnenko Inna; Sydorenko, Tetyana (Current Problems of Sustainable Development, 2026)
The article examines the theoretical, methodological, and applied aspects of proactive marketing as a component of the strategy for increasing the competitiveness of corporate business entities under conditions of an unstable market environment. It is substantiated that the growing turbulence of economic processes, digital transformation, intensified competition, changing consumer behavior, and crisis phenomena require enterprises to shift from a reactive model of market adaptation to a proactive model of marketing behavior aimed at anticipating and shaping market changes. The study clarifies the essence of the concept of proactive marketing, which is proposed to be interpreted as a system of strategically oriented managerial actions focused on identifying, creating, and implementing market opportunities through the formation of new customer value, anticipation of latent consumer needs, and active influence on market demand. Unlike traditional reactive approaches, proactive marketing is aimed not only at responding to changes in the external environment but also at initiating such changes to ensure sustainable market advantages. A conceptual model of the impact of proactive marketing on the competitiveness of corporate business entities is developed. The model substantiates a stepwise mechanism of influence, according to which proactive marketing contributes to demand formation, stimulates revenue growth, enhances operational efficiency, and ultimately strengthens competitive positions. It is argued that competitiveness should be considered not only through financial performance but also through the enterprise’s ability to ensure sustainable development, resilience to market fluctuations, and adaptability to environmental changes. The empirical part of the study is based on a comparative analysis of financial indicators of corporate enterprises operating in different sectors of the Ukrainian economy during 2021–2025. The analysis enabled the classification of enterprises according to the level of marketing proactivity into proactive, adaptive, and reactive groups. A trend has been identified according to which an enterprise with signs of proactive marketing behavior demonstrates more stable development dynamics, higher performance, and more stable competitive positions. The proposed methodological approach may be used as an analytical tool for assessing marketing maturity and improving strategic management practices in corporate business entities.